Beneficial Effect of Edoxaban on Preventing Atrial Fibrillation and Coagulation by Reducing Inflammation via HBG1/HBD Biomarkers - Yang, Chenguang; Wang, Xiang; Guo, Ying; Meng, Xuyang; Li, Yi; Xia, Chenxi; Meng, Lingbing; Dong, Min; Wang, Fang (Frontiers in Pharmacology, 2022)
Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia. Effectiveness and mechanism of Edoxaban in preventing stroke after atrial fibrillation remains unclear. Methods: Expression of HBG1 and HBD in red cells was tested in AF. Sixty C57B/6J mice were randomly divided into control (CON) group, atrial fibrillation (AF) group, AF+Edoxaban group, AF+Rivaroxaban group. HE staining assay and Reticular fiber staining were made. Myocardial fibrosis was evaluated by the masson staining assay, Sirius Red staining assay, immunohistochemical assay for expression of α-SMA and COL1A1. ELISA and RT-PCR assay was performed for the detection of inflammatory parameters (TNF-α, IL1β, IL6, IL10). Blood lipids were detected by the Beckman automatic biochemical analyzer. Furthermore, four items of coagulation were detected, and the molecular docking among the HBG1, HBD, and MASP1 (Xa) was made by the Pymol2.1 software. BP neural network model, cubic spline interpolation, and support vector machine model were constructed to predict prothrombin time based on HBG1 and HBD expression. COIP assay was performed to construct the interaction between the HBG1 and HBD. Functional enrichment analysis was made by DAVID and Metascape. Results: The expression of HBG1 and HBD in red cells of the patients with atrial fibrillation was decreased. The results showed lower level of hemoglobin in red cells with HBG1-siRNA and HBG1-siRNA. Compared with AF group, collagen fiber percentage in AF+Edoxaban group was decreased (P<0.05). After using the Edoxaban, expressions of TNF-α, IL1β, IL6, IL10 were significantly decreased (P<0.05). The LDLC, TC, TG were down-regulated in the AF+Edoxaban group. The PT and APTT in the AF+Edoxaban group was more increasing than the AF mice (P<0.05). Compared with AF group, the expressions of HBG1 and HBD were down-regulated in AF+Edoxaban group (P<0.05). HBG1 protein matched well with HBD and MASP1(Xa) protein surface. There existed significant interaction among the HBG1, HBD, and PT via the BP neural network and support vector machine. Enrichment analysis showed that HBG1 and HBD were mainly enriched in the blood coagulation. Conclusion: Edoxaban could prevent atrial fibrillation and coagulation by reducing inflammation, lipids and fibrosis via HBG1/HBD biomarkers effectively, and the effect was superior to the Rivaroxaban.